2022
DOI: 10.3390/ijerph191710702
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Employees Work Engagement in Small and Medium-Sized Enterprises

Abstract: Background: Improving the labor productivity of small and medium-sized enterprises (SMEs) is essential because of the aging population and predicted reduction in the labor force. Therefore, it is necessary to ensure that employees are in good health to work for long times. In this regard, the purpose of the study is to investigate the relationship between work engagement (WE) and related variables among SME employees. Methods: A cross-sectional study was conducted using the baseline data of the prospective coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…This variable in turn involves a series of dimensions such as vigour (high energy level), dedication (identification with the work), and absorption (concentration on the work) ( 8 ). In this sense, work engagement is an important part of the productivity development of companies, where high standards of job satisfaction, adequate satisfaction with family life, and sufficient self-perceived health are required ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…This variable in turn involves a series of dimensions such as vigour (high energy level), dedication (identification with the work), and absorption (concentration on the work) ( 8 ). In this sense, work engagement is an important part of the productivity development of companies, where high standards of job satisfaction, adequate satisfaction with family life, and sufficient self-perceived health are required ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…The strategy to overcome health problems for SMEs is to integrate several SMEs into a virtual joint venture so as to produce an incentive structure similar to large companies which can increase access to occupational health services and reduce sick visits to clinics (Ahonen et al, 2022). Work engagement (WE) in SME employees is associated with job satisfaction, age, health literacy (HL), and sleep quality (Li et al, 2022). Despite evidence supporting health and wellbeing policies and practices, SMEs still struggle to manage workplace health and present opportunities for improvement (Valsecchi et al, 2023).…”
Section: ) Employee Health and Welfarementioning
confidence: 99%
“…According to a recent study conducted by Li et al (2022), individuals with high levels of motivation tend to exhibit greater productivity. Moreover, this study demonstrated that MSMEs frequently encounter difficulties in maintaining skilled workforce.…”
Section: Employee Engagement and Motivation In Msmesmentioning
confidence: 99%